Acupuncture in persons with an increased stress level-results from a randomized-controlled pilot trial - Wild, Beate; Brenner, Judith; Joos, Stefanie; Samstag, Yvonne; Buckert, Magdalena; Valentini, Jan (PLOS ONE, 2020)
Background In today's Western societies a high percentage of people experience increased or chronic stress. Acupuncture could serve as treatment for persons affected adversely by the increased stress. Methods The AkuRest study was a two-centre randomized controlled pilot study in adult persons with increased stress levels. Participants were randomly allocated to one of three groups: verum acupuncture treatment, sham acupuncture, and a waiting control group. The feasibility of the study was assessed. In addition, effects on stress level (measured by the Perceived Stress Questionnaire (PSQ-20)) and other variables were assessed at the end of treatment and a 3-month follow-up. Results Altogether, N = 70 persons were included in the study. At the end of the treatment 15.7% were lost to follow-up. The adherence to the protocol was good: 82.9% of the participants completed 100% of their treatment. The stress level of the participants was high at baseline (mean PSQ-20 score 75.5, SD = 8.2). Effect sizes (ES) at T1 showed that verum and sham acupuncture were superior to the waiting condition in reducing stress (ES (verum) = -1.39, 95%-CI = [-2.11; -0.67]: ES (sham) = -1.12, CI = [-1.78;-0.44]). At follow-up, effect sizes were in favour of the verum group (as compared to sham). However, confidence intervals and t-tests showed that these differences were not significant. Conclusion The pilot study demonstrated the feasibility of the acupuncture RCT in persons with increased stress levels. Estimated parameters can be used to design a larger RCT to prove the-here indicated-efficacy of verum acupuncture to decrease stress.
Gesehen am 19.11.2020